Gas-liquid chromatography-mass spectrometry of trimethylsilyl ethers of bile alcohols. - G S Tint; B Dayal; A K Batta; S Shefer; F W Cheng; G Salen; E H Mosbach (Journal of Lipid Research, 1978)
This report describes the gas-liquid chromatography-mass spectrometry (GLC-MS) of the trimethylsilyl ethers of 5 beta-cholestane-3 alpha, 7 alpha, 12 alpha-triol with mono- or dihydroxy substitution in the side chain. Compounds with 24- and 25-unsaturation in the side chain were also studied. The gas-liquid chromatographic separation of the different bile alcohols was carried out using 3% QF-1 and 1% HI-EFF 8BP as column packings. Both columns were useful in that the retention times of the trimethyl-silyl ethers of the various 5 beta-cholestanetetrols varied linearly with the position of the side-chain trimethylsiloxyl substituent. The major fragmentations in the GLC-MS of all bile alcohols tested were due to the trimethylsiloxyl side-chain substituent(s). A trimethylsiloxyl group at C-22 was the most effective in promoting side-chain fragmentation, followed, in order of decreasing effectiveness, by substituents at carbons 25, 23, 24, and 26. The side-chain fragments generally gave rise to one or two intense mass peaks and a series of weaker peaks, 90 mass units apart, owing to the loss of successive molecules of trimethylsilanol. Most 5 beta-cholestane-triols, -tetrols, and -pentols can be unequivocally identified by their strong side-chain fragmentation peaks, except for 5 beta-cholestane-3 alpha, 7 alpha, 12 alpha, 26-tetrol, the trimethylsilyl ether of which exhibited very low intensity side-chain fragments.